Tanggung Jawab Pelaku Usaha Tehadap Penetapan Harga Yang Berbeda Atas Produk Sejenis - Dwiyanti Adelin Hetharie; Teng Berlianty; Muchtar Anshary Hamid Labetubun (PATTIMURA Law Study Review, 2023)
ABSTRACT: Along with progress from various aspects, especially progress in the economic sector, facilitating transactions by consumers, the existence of supermarkets adds to consumer satisfaction in shopping, because of its advantages compared to traditional markets. In order to prevent arbitrary actions from occurring on the part of business actors in order to obtain the maximum profit in various ways, including selling similar products at different prices, legislators realize that most business transactions are based on agreements between business actors. The method used in this research is a normative legal research method through a literature study with a conceptual approach and statutory approach. The legal materials used are primary, secondary and tertiary legal materials which are analyzed qualitatively to answer the problems studied. Business actors have the right to set prices for the products sold. In setting prices by business actors, there may be different prices for similar products. Factors that cause price differences for similar products are the negligence of sales clerks in making price adjustments, limited number of employees and deliberate fraud. Business actors are responsible for consumer losses due to price differences in similar products. Consumers are entitled to the right to compensation (compensation) for violations committed by business actors either due to negligence or on purpose. Supermarkets that make price differences on similar products can be subject to administrative sanctions or criminal sanctions. Business actors should be able to run their business properly in accordance with applicable regulations. If a price difference is found for similar products determined by the Business Actor, the Business Actor is proven to have violated Article 8 paragraph (1) letter (f) of Law Number 8 of 1999 concerning Consumer Protection and may be subject to sanctions in the form of imprisonment and fines. Consumers are expected to be more careful and smarter in shopping so as not to be harmed by business actors.